2020
DOI: 10.1101/2020.11.15.20231936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Quarantine Reveals Grade-specific Behavioral Modification of Myopia: One-Million Chinese Schoolchildren Study

Abstract: SummaryBackgroundHigh prevalence of myopia of adolescent has been a global public health concern. Their risk factors and effective prevention methods for myopia across schoolchildren developmental stages are critically needed but remain uncertain due to the difficulty in implementing intervention measurements under normal life situation. We aimed to study the impact of the COVID-19 quarantine on myopia development among over one-million schoolchildren.MethodsWe designed the ongoing longitudinal project of Myop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…These studies found significant increases in the prevalence of myopia in children aged 6−8 years 173 and of myopia progression in primary school children (Grades 1–6). 174 However, these effects were not found in youth.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies found significant increases in the prevalence of myopia in children aged 6−8 years 173 and of myopia progression in primary school children (Grades 1–6). 174 However, these effects were not found in youth.…”
Section: Resultsmentioning
confidence: 97%
“…Sedentary behavior and screen time consistently exhibited large increases across all forms of digital device usage, genders, and ages. Given the significant increases and daily screen times far in excess of guidelines, 65 , 69 , 71 , 77 , 118 , 122 , 143 along with evidence of an increased prevalence of myopia, 173 , 174 this is a particularly concerning finding. Declines in PA and increases in sedentary behavior were both greater among older children and youth.…”
Section: Discussionmentioning
confidence: 99%